2022
DOI: 10.1007/s11661-022-06812-0
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Cast Alloys Based on the Al–Ce–Si–Mg System: An Influence of Silicon on Crystallization, Phase Composition, and Tensile Properties

Abstract: An attempt at strengthening the aluminum-cerium-based alloys through additions of silicon was assessed using the experimental Al5Ce3Si0.5Mg (wt. pct) cast hypoeutectic composition, designed based on the commercial A356 (Al–7Si–0.3Mg, wt pct) grade by substituting a portion of Si with Ce. To determine a role of Si, the Al5Ce0.5Mg (wt. pct) reference was cast and tested under identical conditions. An addition of 3 wt. pct Si to the Al5Ce0.5Mg base increased the room temperature yield stress almost three times, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…As a result, the dislocation density increased, leading to greater dislocation pile-ups near the precipitates and, ultimately, brittle failure. The influence of the CeAlSi 2 phase on the cracking and brittle fracture of Al alloys was reported by Czerwinski and Shalchi Amirkhiz [30] as well. According to the findings, cast Al–Ce alloys lack sufficient mechanical strength and have limited strengthening, making them unsuitable for engineering applications at the moment.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…As a result, the dislocation density increased, leading to greater dislocation pile-ups near the precipitates and, ultimately, brittle failure. The influence of the CeAlSi 2 phase on the cracking and brittle fracture of Al alloys was reported by Czerwinski and Shalchi Amirkhiz [30] as well. According to the findings, cast Al–Ce alloys lack sufficient mechanical strength and have limited strengthening, making them unsuitable for engineering applications at the moment.…”
Section: Resultsmentioning
confidence: 61%
“…Okamoto [12] examined the Al–Ce alloys thermodynamically and proposed the existence of the Al 11 Ce 3 phase in addition to the α-Al phase in Al–12Ce alloys. In contrast, Gröbner et al [39] and Czerwinski and Shalchi Amirkhiz [40] in their research on the solidification thermodynamics of the Al–Ce–Si system suggested the presence of CeAlSi 2 , Al 11 Ce 3 , and α-Al phases when Ce content was greater than 11%.
Figure 2 XRD peaks of (i) Al–12Ce, (ii) Al–12Ce–4Si, and (iii) Al–12Ce–4Si–0.4Mg alloys in the (a) GC and (b) SC conditions; variation of (c) crystallite size, (d) dislocation density, and (e) microstrain values for the GC and SC Al–12Ce–X alloys.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations